Digital divide and accessibility in online education - Romero, Cristina Sánchez; Vacas, Cristina Garcia; Muñoz, Eva María; Levterova, Dora; Lazarov, Andrean (Edelweiss Applied Science and Technology, 2025)
The accelerated transition to online learning, driven by the COVID-19 pandemic, has exposed deep educational inequalities and barriers to access in digital contexts. The purpose of this article is to identify four main types of barriers: digital divide, difficulties in executive and psycho-emotional functions, poor pedagogical design, and limitations in socio-communicative communication, through a systematic review of literature based on the PICO strategy. Findings reveal that limited access to technology, lack of digital literacy, and demotivation caused by inadequate resources hinder the learning experience for many students, especially in vulnerable contexts. The difficulties associated with the lack of social interaction and emotional support in digital environments are also highlighted. Based on the findings, measures such as teacher training, the creation of accessible and flexible content, and the implementation of pedagogical strategies that promote collaboration and inclusion are proposed. In conclusion, this study highlights that not only will tackling these barriers boost the effectiveness of online learning, but they also open up new opportunities to promote more equitable and accessible education.